Single-cell RNA-seq data analysis characterizing bronchoalveolar epithelial cells in patients with SARS-CoV-2 infection - Zhiqin Deng; Qin Li; Yongshen Li; Zhenhan Deng; Xiaoqiang Chen; Zhe Zhao; Guganghui Wang; Daping Wang; Jianquan Liu; Wencui Li (BMC, 2022)
Abstract Background Angiotensin-converting enzyme 2 (ACE2) has been reported to be the main receptor for SARS-CoV-2 infection of host cells. Understanding the changes in bronchoalveolar epithelial cells after SARS-CoV-2 infection of host cells and the intercellular communication relationship between these epithelial cell changes and immune cells is of great significance for the development of therapeutic methods. Methods We explored the single-cell RNA sequence (scRNA-seq) of cells infected with bronchoalveolar lavage fluid (BaLF) of patients with different severities of SARS-CoV-2 and healthy people. Results We found 11 clusters of epithelial cells in the BaLF, and they were derived from the S group. In the S group, the proportion of cells with positive ACE2 expression was relatively high. ACE2 was relatively more expressed in epithelial cell clusters 1, 3, and 7. Clusters 4 and 5 represented the original state, and there were two differentiation directions: one was cluster 2, and the others were clusters 1, 3, and 6. Cluster 7 was the intermediate state. Clusters 1, 3, 6, and 7 had high similarities (> 0.9), and their main signaling pathways focused on inflammatory activation and immune response. Cluster 2 was relatively specific and was up-regulated in differential genes that were mainly related to apoptosis. The ligand-receptor expression pattern of TNFRSF10D-TNFSF10 showed a special inter-cell regulatory relationship between epithelial cell cluster 2 and macrophages. Conclusion This study revealed the changes in epithelial cells derived from alveolar lavage fluid after SARS-CoV-2 infection and the communication relationship with other immune cells.